Equine-Facilitated Counselling and Women with Eating Disorders: Articulating Bodily Experience - Sharpe, Hillary (Canadian Journal of Counselling and Psychotherapy, 2014)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-CA; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-size: 11.0pt; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi;">This hermeneutic phenomenological study explored the experiences of 14 women with eating disorders who took part in an equine-facilitated counselling group. The participants engaged in group and individual interviews that helped to articulate a language for understanding their bodily-relational experiences. Through dialogic movement and communication with their horses, the participants were able to attune in different ways to themselves and their worlds, thus interrupting some of the habitual practices of disordered eating. These changes and the moments that made a difference are explored through a description of the horses and their environment, my reflections as a researcher and counsellor in this context, and a short story pertaining to one of the women and her horse. Implications for counselling theory and practice are discussed.